2020
DOI: 10.3892/etm.2020.9125
|View full text |Cite
|
Sign up to set email alerts
|

Azithromycin combined with doxycycline in non‑gonococcal urethritis

Abstract: Non-gonococcal urethritis (NGU) is one of the most common sexually transmitted diseases caused by chlamydia or mycoplasma. The present study aimed to explore the clinical efficacy of azithromycin combined with doxycycline in patients with NGU and its effect on serum levels of inflammatory cytokine interleukin-6 (IL-6).A total of 98 patients with non-gonococcal urethritis were prospectively selected, of which 46 patients were assigned to an azithromycin group (treated with azithromycin alone), while the rest we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 26 publications
(25 reference statements)
0
3
0
Order By: Relevance
“…Quinolones are recommended as second-line therapeutic drugs, but they are susceptible to produce drug resistance when used alone for a long time. Clinical studies have shown that azithromycin combined with doxycycline is more effective than azithromycin alone, and there was no significant difference in the incidence of adverse reactions between the 2 usages 41 . Sitafloxacin (STFX) is an alternative drug for the treatment of azithromycin-resistant Mycoplasma genitalium .…”
Section: Infectious Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Quinolones are recommended as second-line therapeutic drugs, but they are susceptible to produce drug resistance when used alone for a long time. Clinical studies have shown that azithromycin combined with doxycycline is more effective than azithromycin alone, and there was no significant difference in the incidence of adverse reactions between the 2 usages 41 . Sitafloxacin (STFX) is an alternative drug for the treatment of azithromycin-resistant Mycoplasma genitalium .…”
Section: Infectious Factorsmentioning
confidence: 99%
“…Clinical studies have shown that azithromycin combined with doxycycline is more effective than azithromycin alone, and there was no significant difference in the incidence of adverse reactions between the 2 usages. 41 Sitafloxacin (STFX) is an alternative drug for the treatment of azithromycin-resistant Mycoplasma genitalium . In a clinical trial, the eradication rates of STFX on CT, MG, MH, UU, and Ureaplasma parvum were 96.1%, 71.4%, 100%, 85.7%, and 100%, respectively; STFX was shown to be useful not only for respiratory therapy but also for urinary tract infection, although its drug resistance required further study and observation.…”
Section: Infectious Factorsmentioning
confidence: 99%
“…[ 3 ] Radiotherapy and chemotherapy have been considered main treatments for BC; however, their efficacy falls short of the expectation mainly because of the drug resistance, which is thought as the main cause of cancer recurrence. [ 4,5 ] 5‐Fluorouracil (5‐Fu), a sort of DNA damaging drug which promotes cancer cell apoptosis, has been extensively applied as an anticancer agent in tumors in several vital organs including the colon, head, pancreas, breast, liver, and stomach for decades. [ 6,7 ] However, one previous report clarified that about 30% of BC patients were shown drug resistance when treated with 5‐Fu for the first time.…”
Section: Introductionmentioning
confidence: 99%